ASEAN-China Economic Relations - Saw, Swee-Hock, 1931-2021 (Book collections on Project MUSE., 2007)
Examines the rapidly expanding economic relations between ASEAN and China in recent years. Covers topics such as trade, the ASEAN-China Free Trade Agreement (ACFTA), investments, services trade, energy cooperation, cooperation in developing the Mekong Sub-region, China's aid to Southeast Asian countries, developing stronger business networks, and the political dimensions of China's economic relations with ASEAN.